Improving access to organ donor registration in general practice: a feasibility study - Penn-Jones, Catrin P (Br J Gen Pract, 2020)
BACKGROUND: Organ donor registration helps guide decision making for families. UK general practice provides the facility to register on the NHS Organ Donor Register, but only to new patients. An intervention was developed to present a registration opportunity to existing patients in this setting. AIM: To assess the feasibility and acceptability of an organ donation intervention implemented in UK general practice. DESIGN AND SETTING: The intervention ran in a large practice in Luton in the UK, for 3 months in 2018. A single practice feasibility study was conducted using an embedded experimental mixed methods design. METHOD: Staff were trained to ask patients in consultations if they wished to join the register, and leaflets and posters were displayed in the waiting room. Data on feasibility and acceptability were captured using SystmONE questionnaires, surveys, and focus groups. RESULTS: Over 3 months, in 12.4% of face-to-face consultations, patients were asked if they would like to join the register (812 of 6569), and 244 (30.0%) of these patients joined the register. Common reasons staff did not ask patients were due to telephone consultations, lack of time, and it not being appropriate. Nurses and healthcare assistants performed prompted choice more than doctors (23.4%, 17.1%, and 1.6% respectively). Certain clinic types, such as phlebotomy or routine clinics, facilitated asking compared to those where patients presented with unknown or more serious issues. CONCLUSION: The intervention was found to be feasible and acceptable by some staff and patients. Feasibility criteria were met; therefore, the intervention can progress to further testing.